Evaluating urgent care center referrals to the emergency department. Issue 6 (7th December 2022) - Poyorena, Chris; Patel, Shyam; Keim, Audrey; Monas, Jessica; Urumov, Andrej; Lindor, Rachel; Girardo, Marlene; Rappaport, Douglas
Abstract: Background and objectives: Urgent care centers (UCCs) are increasingly popular with an estimated number of 9600 stand‐alone centers in the United States compared to emergency departments (EDs). These facilities offer a potentially more convenient and affordable option for patients seeking care for a variety of low‐acuity conditions. Because of the limitations of UCCs, patients occasionally are referred to EDs for further care. Prior studies have attempted to evaluate the appropriateness of these UCC referrals. Our study is the first to consider if these referrals require ED‐specific care and the diagnostic concordance of these referrals. Methods: We performed a retrospective chart review to identify patients who were referred from UCCs to our ED between October 2020 and June 2021. We used a Boolean search strategy to screen charts for the terms urgent care, emergency department, referral, or transfer. Cases were manually screened until 300 met the inclusion criteria. Cases had to feature the patient being seen by a UCC provider and directly referred to the ED on the same day. Patients who presented to the ED of their own volition were excluded. Three independent abstractors reviewed the charts. All abstractors and a senior investigator piloted the use of a data collection sheet and discussed the management of any ambiguous data. A senior physician reviewed all discrepancies among abstractors. Data collected included ED final diagnosis and whether the final diagnosis was similar to the UCC diagnosis. A referral was deemed to require ED‐specific care and resources if (1) the patient was admitted, (2) imaging (other than an x‐ray) was performed, (3) specialist consultation was required, or (4) care was provided in the ED that is not conventionally available at UCCs. Results: From the 300 patient charts, 55% of patients referred from UCCs to the ED did not require ED‐specific care or resources and 64% had discordant diagnoses between UCC diagnosis and ED diagnosis. A total of 41% of patients underwent advanced imaging studies, 26% received specialty consultations, and 15% were admitted. Subgroup analysis for lacerations, extremity/fracture care, and abnormal electrocardiograms (ECGs) showed disproportionally high levels of discordant diagnoses and referrals that did not require ED‐specific care or resources. Conclusion: Our data found that 55% of patients referred to EDs from UCCs did not require ED‐specific care or resources and 64% carried a discordant diagnosis between UC and ED diagnosis. We suggest quality remedies, such as educational sessions and engagement with telemedicine sub‐specialists as well as a coordinated formalized system for UCC to ED referrals.